Positive attributes in children and reduced risk of future psychopathology. (January 2015) - Vidal-Ribas, Pablo; Goodman, Robert; Stringaris, Argyris
Abstract : Background: There is little research on children's positive attributes and their association with psychiatric outcomes. Aims: To examine the hypothesis that children's positive attributes are associated with a reduced risk of developing psychopathology in future. Method: Positive attributes, measured with the Youth Strengths Inventory (YSI) and psychiatric outcomes were assessed on two occasions over 3 years in a large epidemiological sample of British children and adolescents ( n = 5325). Results: The YSI showed high to moderate cross-informant correlations and longitudinal stability. Children scoring high on positive attributes at baseline had fewer psychiatric symptoms and disorders at follow-up, adjusting for symptoms at baseline, disorder at baseline and child and family factors. Analyses with propensity score matching also suggested that positive attributes decrease the likelihood of psychiatric morbidity. Conclusions: Children's positive attributes are associated with significantly less psychopathology across time and may be a target for intervention.